The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1007/s10741-021-10170-1
|View full text |Cite
|
Sign up to set email alerts
|

Sodium-glucose cotransporter 2 inhibitors and heart failure: the best timing for the right patient

Abstract: Sodium-glucose cotransporter 2 inhibitors (SGLT2i), initially born as anti-diabetic drugs, have shown many beneficial effects on the cardiovascular system, in particular against heart failure (HF). HF is a complex and multifaceted disease that requires a comprehensive approach. It should not be considered as a simplistic cardiac disease, but a systemic disease that leads to multisystemic organ failure and death. Exploiting their pleiotropic effects, SGLT2i are a very valid tool for HF treatment. Beyond the ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 101 publications
0
17
0
Order By: Relevance
“…Heart failure is a complex and multifaceted disease that leads to multisystemic mechanisms. SGLT2 inhibitors are a very valid tool for HF with reduced ejection fraction (HFrEF) ( 20 ). It is our believe that, due to the current outcomes which did not distinguish the HFrEF and HF with preserved ejection fraction (HFpEF) with the population included, SGLT2 inhibitors may be a possible important role for HFpEF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heart failure is a complex and multifaceted disease that leads to multisystemic mechanisms. SGLT2 inhibitors are a very valid tool for HF with reduced ejection fraction (HFrEF) ( 20 ). It is our believe that, due to the current outcomes which did not distinguish the HFrEF and HF with preserved ejection fraction (HFpEF) with the population included, SGLT2 inhibitors may be a possible important role for HFpEF.…”
Section: Discussionmentioning
confidence: 99%
“…However, all the results reported were regarding a wide spectrum of disease (including HF and renal impairment) manifestations and stages. Recent studies have indicated that it is important to define the best administration timing and the most suitable patients to maximize the SGLT2 inhibitors-derived beneficial effects ( 20 ). Those may provide new perspectives for the management of patients with diabetes along with HF or renal impairment.…”
Section: Discussionmentioning
confidence: 99%
“…However, clinical trials showed a benefit for HF patients with CKD in therapy with MRAs [95]. The nephroprotective action has been robustly demonstrated for SGLT2i [96][97][98]. This paradox highlights another limit in the current four-drug therapy approach, recommended by the latest ESC guidelines [1]: treatment is based on LVEF, and it does not consider the different severity stages of HF and kidney involvement.…”
Section: Heart Failure Therapeutic Management: the Misleading Indicat...mentioning
confidence: 99%
“…Heart failure (HF) is a multisystemic disease characterized by repeated hospitalizations and progressive worsening. The correct follow up and therapy titration, particularly during the vulnerable phases among hospitalizations, remain a main target to improve patients’ prognosis [ 1 , 2 , 3 , 4 ]. The 2021 ESC Guidelines for the diagnosis and treatment of acute and chronic heart failure recommend that patients, after HF hospitalization, should undergo post discharge outpatient clinical visits following a precise timing [ 1 ].…”
Section: Introductionmentioning
confidence: 99%